Principais achados e rendimento diagnóstico da broncofibroscopia de pacientes HIV positivos/AIDS atendidos na Universidade Federal doTriângulo Mineiro - SANTOS, João Paulo Vieira dos (2019)
Bronchoalveolar lavage, brushing and transbronchial biopsy are of fundamental importance in the diagnosis of pathologies affecting the lungs of immunosuppressed patients, especially those with HIV. The aim of the study was to evaluate bronchoscopy procedures performed at the HC-UFTM from 1999 to 2015, to analyze the most frequent findings in HIV-positive patients, to evaluate the diagnostic accuracy of the procedure in these patients and to correlate bronchoscopy results with clinical findings and radiological findings. This was a descriptive and retrospective study, in which the results of washing, brushing and transbronchial biopsy of HIV-positive patients attended at the HC-UFTM from 1999 to 2015 were reviewed. Serologies for HIV were confirmed at the Clinical Pathology Service; cases with negative or unverified serology were excluded. Medical records were reviewed for correlation with clinical and radiological findings. A total of 1423 patients with a mean age of 50 years who underwent the procedure during the study period were selected; 727 cases had no serology for HIV; 696 had serology, 64 being positive. Of these, 47 were men aged 24 to 84 years and 17 women aged 31 to 69 years. The biopsy and cytology tests were positive in 20 (31.25%) of the 64 patients and the most frequent diagnosis was pneumocystosis with 8 cases. Of the 20 cases in which bronchofibroscopy was positive, only 2 did not show agreement between anatomopathological and clinical-radiological diagnoses. The analysis of the cytology and biopsy material obtained by bronchofibroscopy seems to be of value in the etiological diagnosis of pulmonary infections in HIV positive; when positive are confirmed for the presented hypotheses, however, negative results do not always exclude the disease, with clinical and imaging being the guide for therapeutic choice.